Emission of bacterial bioaerosols from a composting facility in Maharashtra, India. (July 2016) - Pahari, Arnab Kumar; Dasgupta, Debdeep; Patil, Rashmi S.; Mukherji, Suparna
Highlights: High concentration of bacterial bioaerosols were observed on-site at the facility. 16–34% of the bacterial bioaerosols collected were in the size range 0.65–2.1 μm. Bioaerosols were dominated by gram positive bacteria, predominantly, Bacillus . Streptococcus, Staphylococcus, Acinetobacter and Kocuria were also observed. Good correlation observed between bacterial bioaerosols and PM10 . Abstract: This study was undertaken to quantify and characterize size-segregated bacterial bioaerosols both on-site and off-site of a waste treatment facility (WTF) in Maharashtra employing windrow composting. Viable bacterial bioaerosols on nutrient agar (NA) and actinomycetes isolation agar (AIA) were quantified after sampling using Anderson-six stage impactor. Viable bacterial bioaerosols were identified based on 16S rDNA sequencing. Approximately, 16–34% of the total viable bacteria collected at the WTF were in the size range 0.65–2.1 μm that can penetrate deep into the respiratory tract and also represents bacteria present in free form. Thus, 66–84% of bacterial bioaerosols were associated with coarse airborne particles greater than 2.1 μm. A total of 24 bacterial species were isolated and characterized through gram staining. Among these 25% were gram negative and 75% were gram positive. The predominant bacterial genera were Bacillus, Streptococcus, Staphylococcus, Acinetobacter and Kocuria . The mean on-site concentration of total viable bacteria on NA and AIA and airborne particles (PM2.5 and PM10 ) were higher than the corresponding off-site values. The mean on-site concentration of viable bacteria on NA and AIA were in the range of 3.8 × 10 3 to 5.4 × 10 4 CFU/m 3 and 9.8 × 10 3 to 1.2 × 10 5 CFU/m 3, respectively, during activity period. Good correlation (R 2 = 0.999) was observed between total bioaerosols and aerosols (PM10 ) collected using Anderson impactor and High volume sampler, respectively. Sampling size segregated aerosols using the Siotus personal cascade impactor indicated higher association of bacteria with the coarse fraction (greater than 2.5 μm).